Physico-chemical Characterization of the Waters of Balobo, Tributary of the Ngiri River, Middle Basin of the Congo River, Democratic Republic of the Congo - Bedi Ngalanza Benjamin; Nyongombe Utshudienyema; Monzambe Mapunzu Paul; Kitambala Kaboka Achille; Inkoto Liyongo Clément; Koto-Te-Nyiwa Ngbolua (Budapest International Research and Critics University, 2023)
A study was conducted between December 2021 and July 2022, to contribute to the physico-chemical characterization of the waters of Balobo, a tributary of the Ngiri River, Middle Congo River Basin in Democratic Republic of the Congo. These waters have particular physico-chemical characteristics: brown waters known to be acidic, with a sour taste, with low light penetration, which raises questions in relation to the diversity and abundance of fish. Some physico-chemical parameters of the water (velocity, flow rate, temperature, pH, Secchi transparency, turbidity, dissolved oxygen, total dissolved solids, ammonium and nitrate) were determined in situ and in the laboratory of the Faculty of Sciences of the University of Kinshasa. The results obtained show that the average morphometric values of the stream are: width (8.10±1.03 m), depth (0.81±0.023 m), velocity (0.094±0.04 m/s) as well as flow (0.59±0.4 m3/s). The water temperature of Balobo varies between 23.9°C and 29.8°C, with an average of 27±1.04°C. The waters of Balobo are brown with low Secchi transparency oscillating between 23 cm and 67 cm, with an average of 46.1±14.6 cm and turbidity especially in the dry season characterized in May by a minimum Secchi of 20 cm and a maximum of 30 cm, with an average of 25.6 cm. Turbidity ranges from 63.4 to 109.8 NTU, with an average of 92.5±14.4 NTU. The waters of Balobo are highly acidic, with pH ranging from 3.1 to 4 with an average of 3.4. Their dissolved oxygen content is very low and varies between 1.03 and 2.7 with an average of 1.62±0.5 mg/L. Total dissolved solids in the Balobo water ranged from 57.1 to 101.3 mg/L with an average of 83.8±15.23 mg/L. Ammonium content in Balobo water ranged from 0.150 to 1.097 mg/L, or an average of 0.613±0.5 mg/L. Nitrate content ranged from 1.02 to 2.06 mg/L with an average of 1.35±0.4 mg/L.